Learning of English literature: ESL pre-service teachers’ perceptions and challenges / Jamiah Baba - Baba, Jamiah (Universiti Teknologi MARA (UiTM), 2022)
Learning of literature, particularly in the ESL context, has been subjected to controversy and consensus. Its proponents argue that literature learning can be beneficial for learners because it provides valuable authentic material and fosters language enrichment, cultural awareness, and personal involvement. Its opponents, however, believe that literature brings its own sets of challenges such as language difficulty and cultural disconnection. As the learning of literature has a direct impact on the learners, it is important to understand how learners view the subject and their experience in learning it. Such understanding can lead to better teaching and learning of literature in ESL classrooms. Hence, this paper attempts to discuss pre-service teachers’ perceptions of, and challenges in, learning literature in a public university in Malaysia. A questionnaire, consisting of multiple-choice items and open-ended questions, was distributed to respondents enrolled in a literature course at the university. Frequency count is used to calculate the response to each question in the single-option format while crosstabulations are used whenever the responses are to be compared with each other. In addition, the learners’ academic grades are analysed and cross-tabulated with the items in the questionnaire. The findings show that the learners have positive perceptions of literature and admitted to having enjoyed learning literature in the course due to several factors, including the role of the instructor. These findings have implications on how educators plan and teach literature courses, which will affect how ESL learners approach and learn literature.